Comparison of Student Learning Outcomes in Terms of ‘Digital Immigrant-Native’ Teachers Learning Methods - Taku Neno, Khatrin Juliani; Sudira, Putu; Daryono, Rihab Wit (Journal of Education Reseach and Evaluation, 2022)
As technology continues to evolve, the gap between those who have grown up with technology (digital natives) and those who have not (digital immigrants) continues to widen. Therefore, this research aims to analyze the comparison of students learning outcomes taught by two different groups of teachers from different generation (digital native and digital immigrant). The subjects of this research were 10th-grade students in the Department of Computer and Network Engineering at Vocational High School. The total of the research respondents were 60 students. This research was using a quantitative approach with a comparative method. The data collected was the form of a questionnaire and a summary of the scores in the last semester. The results of the independent sample t-test obtained a Sig. (2-tailed) value of 0.065 > 0.05, so the decision making in the Independent Sample t-test, concluded that the null hypothesis (Ha) was accepted and the alternative hypothesis (Ha) rejected. Ho is a hypothesis which states that there is no correlation or influence between variables and other variables, while Ha is a hypothesis which states that there is a correlation or influence between variables and other variables. Based on the research result, it means that there is no difference in learning outcomes between students taught by digital immigrant teacher and digital native teacher. This research proves that digital native teachers and digital immigrant teachers are equally qualified.